De la producción de TV a la comunicación para el desarrollo - Beingolea Delgado, Eduardo Guillermo (2021)
This report is the result of a professional retrospective of more than 30 years of constant experiences through which destiny wide fields of communication, from production for the media, the development of successful national and international television projects, the realization of events with high media impact, the development of the communications from social projects for the economic improvement of rural Amazonian communities to the communicational coordination for a project for international cooperation with the migrant community. The work experiences that I describe made me know the whole country and took me beyond our borders and showed the success achieved in the different programs, projects and jobs that I execute and design, being able to use what I learned in my time at university with criteria. I am very grateful and I consider myself fortunate to have been able to get to know our reality closely and have to served many compatriots and communities of that deep Peru that we need to reach